2015
DOI: 10.3758/s13415-015-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Graded expectations: Predictive processing and the adjustment of expectations during spoken language comprehension

Abstract: The goal of this study was to investigate the use of local and global context to incoming words during listening comprehension. Local context was manipulated by presenting a target noun (e.g., cake, veggies) that was preceded by a word that described a prototypical or atypical feature of the noun (e.g., sweet, healthy). Global context was manipulated by presenting the noun in a scenario that was consistent or inconsistent with the critical noun (e.g., a birthday party). ERPs were examined at the feature word a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
59
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 60 publications
16
59
2
Order By: Relevance
“…Accompanying this effect, DeLong et al (2011), as well as DeLong et al, (2012, 2014a), reported a late (post-N400) sustained frontal, somewhat left ERP positivity to low cloze probability but plausible continuations of highly constraining sentence contexts (e.g., airplane in the previous example). This positivity also has been reported by others, under similar experimental circumstances, to unexpected but acceptable continuations in sentences or discourses (Federmeier et al, 2007; Thornhill and Van Petten, 2012; Moreno et al, 2002; Coulson and Van Petten, 2007; Kutas, 1993; Brothers et al, 2015; Boudewyn et al, 2015). …”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Accompanying this effect, DeLong et al (2011), as well as DeLong et al, (2012, 2014a), reported a late (post-N400) sustained frontal, somewhat left ERP positivity to low cloze probability but plausible continuations of highly constraining sentence contexts (e.g., airplane in the previous example). This positivity also has been reported by others, under similar experimental circumstances, to unexpected but acceptable continuations in sentences or discourses (Federmeier et al, 2007; Thornhill and Van Petten, 2012; Moreno et al, 2002; Coulson and Van Petten, 2007; Kutas, 1993; Brothers et al, 2015; Boudewyn et al, 2015). …”
Section: Introductionsupporting
confidence: 89%
“…Some of this work has relied on the N400 ERP component, a negative-going waveform peaking around 400 ms post-stimulus onset, which is part of the brain’s normal response to semantic processing of a meaningful stimulus in context. N400 studies have uncovered evidence for semantic prediction at various levels, e.g., for lexical, categorically-related, event-related, and conceptually similar information (e.g., DeLong et al, 2005; Thornhill and Van Petten, 2012; Federmeier and Kutas, 1999a; Metusalem et al, 2012; Boudewyn et al, 2015). In conjunction with these findings, there is also growing support for the idea that there may be processing consequences, when predictions are not validated by the input.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This knowledge may be important in processing incoming words even if the words themselves are not predictable in context. Boudewyn, Long, and Swaab (2015) examined the processing of nouns (e.g., cake) that were plausible in context, but had low cloze probabilities in their specific contexts. They found that semantic features of the word that were relevant to the context (e.g., sweet) were activated before the word was received, even when that word could not be predicted.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, statements that clash with world knowledge stored in long-term memory elicit an N400 response. However, the most recent views on what the N400 indexes highlight its role as a sign that online predictions are being made about upcoming words in discourse (Boudewyn, Long, & Swaab, 2015;Otten, Nieuwland, & Van Berkum, 2007;Van Berkum, Brown, Zwitserlood, Kooijman, & Hagoort, 2005;Wicha, Moreno, & Kutas, 2004). Thereafter, the N400 is not as sensitive to truthvalue computations as it is an online predictor for upcoming information based on world knowledge (Nieuwland, 2015;Nieuwland & Kuperberg, 2008).…”
mentioning
confidence: 99%